CHRONIC FATIGUE SYNDROME – AN INSIGHT THROUGH ĀYURVĒDA - Dr. Kavya. K; Dr. Shreevathsa, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Chronic fatigue syndrome (CFS) is one among the thriving issue worldwide. It results mainly due to stressful & deranged food & life style habits. There is no as-such mentioning of disease details in Āyurvēda saṁhitā granthās. To fill this gap, based on the guidelines mentioned in saṁhitās for understanding Anukta vyādhi, one can understand the CFS too. Nidāna pañcaka is one among the mandatory criteria for any vyādhi. Here also same methodology followed to understand CFS in terms of Āyurvēda. It is proposed that CFS is to be understood as Vāta pradhāna Tridōṣa duṣṭi condition which mainly follows Vātavyādhi & Ōjō duṣṭi nidāna & Lakṣaṇas. Based on the involvement of nidāna, dōṣa, dushya, lakṣaṇa etc diagnose CFS in Initial stages as Rasa or Rakta pradōṣaja vikāra. / Type of sannipātaja Kṣaya / Anukta Vāta vyādhi. In later stages: Majja Pradōṣaja vikāra. / Ōjō duṣṭi.